Book review: Geological records of tsunamis and other extreme waves, by M. Engel, J. Pilarczyk, S.M. May, D. Brill & E. Garrett (Eds.), 2020. Elsevier Inc., Amsterdam. 848 pages. Paperback: price €156,19, ISBN 9780128156865; e-Book: price €156,19, ISBN 9780128156872 - Stattegger, Karl (Geologos, 2021)
Book review: Geological records of tsunamis and other extreme waves, by M. Engel, J. Pilarczyk, S.M. May, D. Brill & E. Garrett (Eds.), 2020. Elsevier Inc., Amsterdam. 848 pages. Paperback: price €156,19, ISBN 9780128156865; e-Book: price €156,19, ISBN 9780128156872